2021
DOI: 10.1136/jitc-2020-001941
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin enhances BCG-specific γδ T cells during intravesical BCG therapy for non-muscle invasive bladder cancer: a randomized, double-blind study

Abstract: BackgroundAlthough intravesical BCG is the standard treatment of high-grade non-muscle invasive bladder cancer (NMIBC), response rates remain unsatisfactory. In preclinical models, rapamycin enhances BCG vaccine efficacy against tuberculosis and the killing capacity of γδ T cells, which are critical for BCG’s antitumor effects. Here, we monitored immunity, safety, and tolerability of rapamycin combined with BCG in patients with NMIBC.MethodsA randomized double-blind trial of oral rapamycin (0.5 or 2.0 mg daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…49 CD122 (to which IL-2c directs IL-2) is expressed on conventional T (CD4 + and CD8 + ), NK, and γδ T cells, all of which are important in localized human BC treatment with BCG. 50 We explored immune cell contributions to IL-2c and αPD-L1 treatment success in mouse BC models and found that surprisingly, conventional T cells, specifically CD8 + T cells, were dispensable for IL-2c treatment effects, despite their necessity for αPD-L1 efficacy here, as also shown by others. 24 As CD8 + T cell content in BC is a favorable prognostic indicator, 25 the relative independence of IL-2c efficacy on CD8 + T cells in orthotopic BC and reliance on γδ T cells that do not affect αPD-L1 efficacy suggests that these agents could combine clinically for improved treatment efficacy.…”
Section: Discussionsupporting
confidence: 70%
“…49 CD122 (to which IL-2c directs IL-2) is expressed on conventional T (CD4 + and CD8 + ), NK, and γδ T cells, all of which are important in localized human BC treatment with BCG. 50 We explored immune cell contributions to IL-2c and αPD-L1 treatment success in mouse BC models and found that surprisingly, conventional T cells, specifically CD8 + T cells, were dispensable for IL-2c treatment effects, despite their necessity for αPD-L1 efficacy here, as also shown by others. 24 As CD8 + T cell content in BC is a favorable prognostic indicator, 25 the relative independence of IL-2c efficacy on CD8 + T cells in orthotopic BC and reliance on γδ T cells that do not affect αPD-L1 efficacy suggests that these agents could combine clinically for improved treatment efficacy.…”
Section: Discussionsupporting
confidence: 70%
“…A recent study confirmed that BCG induces T cell dependent tumor-specific immunity and suggested that BCG-specific γδT cells are required for induction of tumor-specific immunity mediated by conventional αβT. In this study, enhancement of γδT cell responses by treating mice with the mTOR inhibitor rapamycin enhanced the efficacy of BCG [80], a finding that has prompted clinical studies of this combination [81].…”
Section: Bcg-specific Versus Tumor-specific Immunitysupporting
confidence: 67%
“…Thus, strategies to boost function of either cell type could improve IL-2c efficacy, such as ultra-low dose rapamycin, which we demonstrated to be a safe and tolerable γδ T cell adjuvant in early phase BC trials when combined with BCG immune therapy. 45 …”
Section: Discussionmentioning
confidence: 99%